2015
DOI: 10.1111/apha.12632
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mitogen‐activated protein kinase 1/2 in the acute phase of stroke improves long‐term neurological outcome and promotes recovery processes in rats

Abstract: It is demonstrated that benefits of early treatment with U0126 persist beyond subacute phase of ischaemic stroke in male rats. Prevention of ERK1/2 activation in the acute phase results in improved long-term functional outcome and enhances later-stage recovery processes. These results expand our understanding of the benefits and promise of using MEK1/2 inhibitors in stroke recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…The immunostaining did not double stain with NeuN or overlap with nestin immunolabelling indicating that Ki67 + cells are not neurons or astrocytes. In a previous study, we demonstrated that nestin is expressed in astrocytes because Glial fibrillary acid protein (astrocyte marker) double‐stained with nestin . Similar staining was performed in this study and confirmed our previous results (data not shown).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The immunostaining did not double stain with NeuN or overlap with nestin immunolabelling indicating that Ki67 + cells are not neurons or astrocytes. In a previous study, we demonstrated that nestin is expressed in astrocytes because Glial fibrillary acid protein (astrocyte marker) double‐stained with nestin . Similar staining was performed in this study and confirmed our previous results (data not shown).…”
Section: Discussionsupporting
confidence: 92%
“…This study is the first to demonstrate that there is a clear association between post‐stroke recovery and vascular changes in stroke. In previous studies, it is demonstrated that U0126 acutely did not alter any physiological parameters . Specific blockade of the MEK‐ERK1/2 pathway with U0126 improved long‐term functional outcome, normalized cerebral perfusion and promoted recovery processes despite administration of the inhibitor as late as 6 hours after reperfusion, a clinical relevant time‐point.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Presently, MCAO results in enhanced expression of pERK1/2 in smooth muscle cells of the ischaemic middle cerebral artery and associated small arteries (shown by colocalization with actin) but not in surrounding brain tissue; U0126 blunts this activation in parallel with a reduction in infarct volume and an improved neurological score (Mostajeran et al . ). The other MAPK p38 and JNK were only mildly affected in vessel walls by MCAO; however, as shown before there is enhanced pp38 and pJNK in brain tissue subsequent to stroke that is mainly localized to neurones and glial cells, and this occurs late in the process (Maddahi & Edvinsson ).…”
mentioning
confidence: 97%
“…In this issue of Acta Physiologica, Mostajeran and colleagues provide evidence that acute treatment of U0126, a MEK1/2 inhibitor, improved long-term outcome of neurological deficits in a rodent male experimental stroke model (Mostajeran et al 2015). Furthermore, a correlation between infarct size and recovery processes in rats treated with U0126 or vehicle (DMSO) was observed.…”
mentioning
confidence: 99%